2016
DOI: 10.7717/peerj.1654
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes in diapause or quiescent potato cyst nematode,Globodera pallida, eggs after hydration or exposure to tomato root diffusate

Abstract: Plant-parasitic nematodes (PPN) need to be adapted to survive in the absence of a suitable host or in hostile environmental conditions. Various forms of developmental arrest including hatching inhibition and dauer stages are used by PPN in order to survive these conditions and spread to other areas. Potato cyst nematodes (PCN) (Globodera pallida and G. rostochiensis) are frequently in an anhydrobiotic state, with unhatched nematode persisting for extended periods of time inside the cyst in the absence of the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…pallida , Palomares-Rius, et al . 31 confirmed that several hundred genes were differentially expressed after 4 days of exposure to TRD.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…pallida , Palomares-Rius, et al . 31 confirmed that several hundred genes were differentially expressed after 4 days of exposure to TRD.…”
Section: Discussionsupporting
confidence: 54%
“…Palomares-Rius, et al . 31 also found that expression of many transmembrane transporter genes was significantly increased when hydrated G . pallida cysts were exposed to TRD.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is estimated that PPNs reduce crop yields by 12.3%, equating to an estimated $US 80–157 billion in losses each year 3638 . PPNs respond transcriptionally, physiologically and behaviourally to plant root exudates, using exudates to trigger egg hatching, and to facilitate host-finding 31,35,3943 . Understanding the molecular, chemical and physiological mechanisms underpinning both root exudation and PPN interactions could facilitate the development of aggressive new ex planta control strategies for sustainable intensification of global agriculture, through breeding, rhizosphere engineering and/or biotechnology 4447 .…”
Section: Introductionmentioning
confidence: 99%
“…Transcriptomic study allows reduction of genomic complexity by sequencing only coding regions, in which a large proportion of significantly functional variants are expected, also allowing identification of genes whose expression or allelic frequency can be correlated to a specific characteristic [26]. Other studies have focused on the discovery of effectors in plant-parasitic nematodes, including PCNs [2731], as well as on the transcriptomic study of different pathotypes [14] or life stages [32, 33] of G. rostochiensis and G. pallida , but to our knowledge, a direct transcriptomic comparison of pathogenic and non-pathogenic Globodera species on potato has never been done. The aims of this study were to characterize the transcriptomic differences between four Globodera species exposed to potato root diffusate and to identify genes putatively involved in host specificity, using RNA sequencing to look at changes in gene expression and genetic variation between populations.…”
Section: Introductionmentioning
confidence: 99%